Drifting house - Lee, Krys. (New York : Viking, 2012)
Spanning Korea and the United States, from the postwar era to contemporary times, the stories presented in "Drifting House" illuminate a people torn between the traumas of their collective past and the indignities and sorrows of their present.
A temporary marriage -- At the edge of the world -- The pastor's son -- The goose father -- The salaryman -- Drifting house -- A small sorrow -- The believer -- Beautiful women.
Keywords: Korean Americans -- Fiction; Koreans -- Fiction; Immigrants -- United States -- Fiction; Korea -- Fiction; Short stories